Hydrodynamic response of Tension Leg Platform with damaged tendon - Mohd Zamri, Qistina (Universiti Teknologi PETRONAS, 2019)
In this study, a tension leg platform is modelled, and a simulation is done to get its hydrodynamic responses by using a STAR-CCM+ software. The aim of the study is to get the hydrodynamic responses of the tension leg platform with tendon damage. From the results of the past papers, the results of the 6 degrees of freedom of Tension leg platform have been identified in their study. The parameters in modelling the Tension Leg platform has been taken in past paper. From that, the modelling and simulation is taken into the software. From the results, the responses will explain the ability or limitation of the Tension Leg Platform with damaged tendon and it will compare with a fully working tendons. After interpretation and discussion, the hydrodynamic response of Tension Leg platform with damaged tendon will obtain. A hydrodynamic analysis is conducted to prove the structure’s dynamically stabilities.